2019
DOI: 10.21037/atm.2019.01.69
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics and treatment strategies for young lung cancer patients

Abstract: Background: The reported age-specific survival rates of lung cancer patients have been largely inconsistent. Management strategies for younger patients and treatment outcomes are not well characterized. Methods: Out of the 4,697 lung cancer patients with treatment history at Tokyo Medical University Hospital between January 2000 and December 2014, 266 patients were <49 years of age. Patient characteristics were investigated, and the association of overall survival (OS) with age, sex, stage, and histological ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 25 publications
(35 reference statements)
5
20
1
Order By: Relevance
“…squamous cell carcinoma and SCLC ranked the second and third most common subtype in the younger group 40 42 . A relatively high percentage of patients had advanced-stage disease at diagnosis in our study (greater than 50% of all patients), which was consistent with previous studies 12 , 43 .…”
Section: Discussionsupporting
confidence: 93%
“…squamous cell carcinoma and SCLC ranked the second and third most common subtype in the younger group 40 42 . A relatively high percentage of patients had advanced-stage disease at diagnosis in our study (greater than 50% of all patients), which was consistent with previous studies 12 , 43 .…”
Section: Discussionsupporting
confidence: 93%
“…We found 45 retrospective studies on AYAs with lung cancer. 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 Fourteen were reports from national databases. Our final selection for genomic profiling in AYA with lung cancer included 23 studies 4 , 7 , 8 , 9 , 11 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 40 , 41 , 43 , 44 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“… 39 In patients with lung cancer, many studies that compare smoking history between young and old patients found significantly less exposure to tobacco in young lung cancer patients. 4 , 7 , 11 , 14 , 15 , 17 , 19 , 21 , 23 , 24 , 28 , 37 , 40 , 43…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations